EXTERNAL STATE FINANCIAL CONTROL IN THE REPUBLIC OF TUVA. PRIORITIES IN PLANNING CONTROL ACTIVITIES - V. K. Khomushku; M. R. Kara-Sal (Вестник университета)
Features and problems of planning external state financial control have been considered. Characterization of key functional directions of activity has been given and the essence of the complex powers exercised by the accounting chamber of the Republic of Tuva has been revealed. Legislatively approved procedure for planning the activities of the Republican control and accounting structures has been analyzed in detail. Factors influencing the process of preparation of planning documents have been identified, the development of the work plan has been described and the main groups of activities in the area of financial control and audit of the accounts chamber of the Republic of Tuva have been highlighted. It has been noted, that one of the important activities of the main control body is expert and analytical work. Functions of the accounting chamber as one of the important participants in the process of state strategic planning have been revealed. According to the results of the analysis of planning of activity of control and accounting body, the main reasons and the factors influencing efficiency of activity have been defined. Conclusion has been made about the need to improve the planning process of the system of external state financial control of the Republic of Tuva.